Analysis of Household Poverty Risk Factors - Madris; Maharajabdinul; Roy, Juliansyah (Fakultas Ekonomi dan Bisnis Universitas Mulawarman, 2024)
The study aimed to identify and analyze the stimulating poverty risk factors in urban households, South Sulawesi Province, which included demographic, social, and economic characteristics. The population was poor households in urban areas in South Sulawesi Province. This research used a logistic regression analysis method. The results of data analysis exhibited that social characteristics, such as the quality of human resources, were the main stimulus factor for household poverty risk. Meanwhile, the aspects of economic and demographic did not contribute to the stimulus factors in reducing household poverty risk in urban residents in South Sulawesi Province. Education alone was not enough to increase individual income but rather decisive work experience.